Indicators of vaccination status in patients with chronic kidney disease: the importance of recommendations from healthcare providers - Gizem Kumru; İrem Akdemir; Cengiz Kaan Demir; Kenan Ates; Sehsuvar Erturk; Gokhan Nergizoglu; Kenan Keven; Sim Kutlay; Sule Sengul (BMC Nephrology)
Abstract Background Influenza and pneumococcal vaccinations are strongly encouraged for individuals with chronic kidney disease (CKD); however, vaccination rates remain below the target. Establishing factors influencing vaccination status may guide approaches to enhance vaccine uptake among this vulnerable patient population. Methods A cross-sectional study involved 307 patients diagnosed with CKD for at least one year (40.4% non-dialysis, 37.1% dialysis, and 22.5% kidney transplantation). Demographic data, clinical conditions, and social factors, such as nutritional status, frailty, and health literacy, were evaluated. The vaccination rates for influenza, and pneumococcus, along with the associated variables, have been analyzed. Results The average age of the patients was 57 years (± 16), with a predominance of males (56.7%). The percentages of individuals unvaccinated for influenza, pneumococcus, and SARS-CoV-2 were 61.9%, 60.9%, and 5.9%, respectively, while only 11 patients (3.9%) received an annual influenza vaccine. Healthcare providers recommended influenza and pneumococcal vaccination to 60.3% and 37.1% of patients, 71% of whom visited a physician 5 or more times a year, respectively. The frequency of regular or infrequent influenza vaccination was significantly correlated with healthcare providers’ recommendations (HR, 14.348; 95% CI, 6.842–30.086; p < 0.001), increased risk of malnutrition (HR, 2.722; 95% CI, 1.467–5.050; p:0.002), and previous pneumococcal vaccination (HR, 2.100; 95% CI, 1.180–3.737; p:0.012). Conversely, frailty was linked to reduced vaccination rates (HR, 0.198; 95% CI, 0.083–0.472; p < 0.001). In multivariable models, healthcare providers’ recommendations (HR, 17.804; 95% CI, 9.353–33.892; p < 0.001) and advanced age (HR, 1.024; 95% CI, 1.001–1.046; p:0.040) were determined as factors associated with pneumococcal vaccination. Conclusion The guidance of healthcare professionals is the key factor in improving immunization rates. Developing health policies that consider factors influencing vaccine hesitancy and engage healthcare providers in the decision-making process is essential. Clinical trial number Not applicable.